(untitled) (Baghdad Science Journal, 2023)
Many studies of the relationship between COVID-19 and different factors have been conducted since the beginning of the corona pandemic. The relationship between COVID-19 and different biomarkers including ABO blood groups, D-dimer, Ferritin and CRP, was examined. Six hundred (600) patients, were included in this trial among them, 324 (56%) females and the rest 276 (46%) were males. The frequencies of blood types A, B, AB, and O were 25.33, 38.00, 31.33, and 5.33%, respectively, in the case group. Association analysis between the ABO blood group and D-dimer, Ferritin and CRP of COVID-19 patients indicated that there was a statistically significant difference for Ferritin (P≤0.01), but no-significant differences for both D-dimer and CRP. biomarkers. Regarding the age association between COVID-19 patients and biomarkers, D-dimer and Ferritin levels showed a significant difference (P≤0.01), (P≤0.05) in sequence, between ages. Meanwhile CRP level was non-significant. Considering the gender effect on biomarkers on COVID-19 patients, D-dimer and Ferritin males were significant (P≤0.05), (P≤0.01) in sequence from females. But no-significant effect of CRP level. Our results proved that age is an important factor in the COVID-19 infection’s development. The evidence of the association between ABO blood group, D-dimer, CRP and Ferritin with COVID-19 severity, progression and susceptibility, is important and requires more investigation.